The Role of ChatGPT and Artificial Intelligence in Physical Therapy and How It Would Impact Employment in This Field: A Conversation with ChatGPT - Qadeer, Ummara (Jurnal Medis Islam Internasional, 2024)
Introduction: ChatGPT is a generative language model tool launched by OpenAI on November 30, 2022, enabling the public to converse with a machine on various topics. In January 2023, ChatGPT reached over one hundred million users, making it the fastest-growing consumer application. Objective: This interview with ChatGPT provides an idea of the current capabilities of ChatGPT and AI to play their role in the physical therapy field and how it can impact the employment rate in the physical therapy field. It also hints at current problems and limitations it will face in providing services in physical therapy. In this conversation with ChatGPT, this study will make ideas on how AI can become more helpful for Physical Therapists, how the quality of treatment cannot be compromised even by means of ChatGPT and AI, and how it impacts employment in the field of physical therapy. Methods: OpenAI provided ChatGPT-3.5 was used in the paper to make content about its application in the field of physical therapy and how it would impact employment in this field. This is done through self-centered questions about the current capabilities of ChatGPT and AI to play their role in the physical therapy field. Results: ChatGPT and AI can be supportive tools for physical therapists, but they cannot completely replace physical therapists. Physical therapists are likely to accomplish better treatment outcomes compared to AI. Conclusions: AI offers considerable advantages for physical therapists, improving efficiency and accuracy in documentation writing and other things and it is time saving for them. Currently, as per need physical therapists should integrate training of AI in their education and practice. Ethical considerations like privacy of patient’s data, informed consent and liability must remain essential.AI counters human expertise, it should be assessed as a supportive tool rather than a replacement. AI is unlikely to affect employment of physical therapists, as this field requires human empathy, hands on techniques and personalized care that technology cannot replicate.